Evaluasi Performa dan Kesesuaian Uji Antara Uji Aglutinasi Toxoplasma Modified Agglutination Test dengan Berbagai Kit Uji Serologis Komersial - Valinata, Sisca; Sulinawati, Sulinawati; Subekti, Didik Tulus (Jurnal Veteriner, 2020)
Toxoplasmosis is a zoonotic disease and known as Food borne diseases as main transmission pathway in Indonesia. Regular monitoring of animal health with surveillance is very important and requires a diagnostic devices that have good accuracy and continuous availability at affordable costs. Serological testing techniques with agglutination method are suitable and appropriate choices because they are quite accurate and simple in their application and does not require skilled human resources. Aims of study aims are to develops an agglutination test kit and evaluate its performance comparatively with several commercial kits. 98 samples of positive and negative standard serum that have been confirmed by using 4 commercial serological kits were used to evaluate the inhouse-toxoplasma modified agglutination kit (ToMAT). Furthermore 186 field serum samples were used in inter reliability agreement assay for comparing the ToMAT kit with four commercial kits available in Indonesian market’s and immunoblotting. Performance evaluation of the ToMAT shows the sensitivity, specificity and diagnostic accuracy, were 98.55%; 86.21% and 94.9% respectively. The value of PPV and NPV is 94.4%; 96.2%. The ToMAT test kit had a good agreement with immunoblotting (76%) and the Toxotest ELISA kit (74.1%) was based on the value of Gwet’s AC1.